2008
DOI: 10.1016/j.devcel.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cthrc1 Selectively Activates the Planar Cell Polarity Pathway of Wnt Signaling by Stabilizing the Wnt-Receptor Complex

Abstract: Vertebrate Wnt proteins activate several distinct pathways. Intrinsic differences among Wnt ligands and Frizzled (Fzd) receptors, and the availability of pathway-specific coreceptors, LRP5/6, and Ror2, affect pathway selection. Here, we show that a secreted glycoprotein, Cthrc1, is involved in selective activation of the planar cell polarity (PCP) pathway by Wnt proteins. Although Cthrc1 null mutant mice appeared normal, the introduction of a heterozygous mutation of a PCP gene, Vangl2, resulted in abnormaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
276
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(285 citation statements)
references
References 43 publications
(59 reference statements)
4
276
1
1
Order By: Relevance
“…Aside from the presence or absence of Ryk and Ror2, other factors can bias Wnt5a to act through a canonical or non-canonical response. For example, a secreted collagen protein, Cthrc1, can potentiate the Wnt-Ror2-Fz interaction, enhancing PCP signaling of Wnt5a 55 . Conversely, there are also non-Wnt ligands for the Frizzled receptors, such as Norrin 56 , that can activate the canonical pathway.…”
Section: Non-frizzled Wnt Receptorsmentioning
confidence: 99%
“…Aside from the presence or absence of Ryk and Ror2, other factors can bias Wnt5a to act through a canonical or non-canonical response. For example, a secreted collagen protein, Cthrc1, can potentiate the Wnt-Ror2-Fz interaction, enhancing PCP signaling of Wnt5a 55 . Conversely, there are also non-Wnt ligands for the Frizzled receptors, such as Norrin 56 , that can activate the canonical pathway.…”
Section: Non-frizzled Wnt Receptorsmentioning
confidence: 99%
“…The immunoprecipitates or whole-cell lysates were separated by SDS-PAGE and blotted onto PVDF membranes. The primary antibodies were as follows: anti-His and anti-FLAG M2 (24).…”
Section: Methodsmentioning
confidence: 99%
“…Ror2 has been shown to act as a receptor or co-receptor for Wnt5a (Oishi et al, 2003;Mikels and Nusse, 2006;Nishita et al, 2006). In fact, both Ror2-and Wnt5a-mutant mice showed similar skeletal, cardiovascular, genital and inner ear abnormalities that are caused at least partly by disrupted planar cell polarity and convergent extension movements during development (Qian et al, 2007;Yamamoto et al, 2008). It has been shown that Ror2 mediates Wnt5a signaling by activating the Wnt/JNK pathway and inhibiting the b-catenin-TCF pathway (Oishi et al, 2003;Mikels and Nusse, 2006).…”
Section: Introductionmentioning
confidence: 99%